Mitochondrial-targeted Hsp90 C-terminal inhibitors manifest anti-proliferative activity. Issue 22 (15th November 2019) - Zhang, Zheng; Banerjee, Monimoy; Davis, Rachel E.; Blagg, Brian S.J.
Graphical abstract: Abstract: The development of C-terminal heat shock protein 90 kDa (Hsp90) inhibitors has emerged as a potential treatment for cancer. Similarly, small molecules that target the mitochondria have proven to be efficacious towards cancer, as the reprogramming of mitochondrial function is often associated with oncogenic transformation. Herein, we report the development of triphenylphosphonium (TPP)-conjugated Hsp90 C-terminal inhibitors, their anti-proliferative activity, and accumulation in the mitochondria. In general, TPP-conjugated Hsp90 C-terminal inhibitors were found to manifest increased activity against various cancer cell lines when compared to the parent compounds.